Rapid Apical Healing with Simple Obturation Technique in Response to a Calcium Silicate-Based Filling Material - Bahaa AlBakhakh; Aqeel Al-Saedi; Riad Al-Taee; Mohammed Nahidh (Hindawi Limited, 2022)
Background. Root canal sealers with high alkaline (pH more than 11) and bioactive properties (release ions) are more effective for healing the apical area and preventing reinfection in root canals. Pure calcium silicate-based bioceramic premixed injectable sealers lead to change the obturation technique because it depends on maximizing amount of sealer and single cone gutta-percha as a carrier. This retrospective clinical study aimed at demonstrating the effect of single cone gutta-percha with a calcium silicate-based filling, used to fill the root canal in a single visit, on the apical healing with different lesion size. Materials and Methods. 195 patients needing root canal treatment were treated at the Al-Jazaer private clinic in southern Iraq. Cases were obtained during the 2017-2021 period (retrospective study). All patients were treated with a simple hydraulic condensation technique that used calcium silicate-based filling materials as the sealer with single cone gutta-percha as the carrier, with a minimum follow-up period of approximately one year. Both treatment- and patient-related factors were evaluated. The clinical outcomes depended on classification with respect to complete (success) or incomplete (failure) healing. Statistical analysis was performed using a chi-square test to compare different related factors. Results. Radiographs for 195 patients were examined, and the average follow-up time was 20.44 months. The complete healing success rate was 164 (84.1%), and 31(15.9%) patients were not healed. The highly significant success rate was 88.7% for the initial treatment compared with 63.9% for retreatment. Small and medium lesions (<5 mm diameter) had a significant success rate compared to large lesions (>5 mm diameter). Sealer extrusion was found in 68.7% of cases, but it did not have any significant effect on the treatment result. Conclusions. The bioceramic calcium silicate-based filling sealer used with single-cone gutta-percha led to increased success of apical healing with a simple hydraulic condensation technique without multiple visit treatments and premedication material.